Normative data for the Digit Symbol Substitution Test for diverse Hispanic/Latino adults: Results from the Study of Latinos‐Investigation of Neurocognitive Aging (SOL‐INCA). (20th December 2022) - Paredes, Alejandra Morlett; Tarraf, Wassim; Gonzalez, Kevin A; Stickel, Ariana M; Graves, Lisa V.; Salmon, David P.; Kaur, Sonya; Gallo, Linda C; Isasi, Carmen R; Lipton, Richard B.; Lamar, Melissa; Goodman, Zachary T; et al.
Abstract: Background: Neuropsychological assessment plays an important role in identifying mild cognitive impairment and dementia; demographically appropriate norms are essential for interpreting test performance and maximizing diagnostic accuracy. Limited availability of normative data for cognitive tests administered to older Hispanic/Latino adults can lead to diagnostic error. Executive functioning and information processing speed are crucial elements of neuropsychological assessment. To meet the needs of the Hispanic/Latino population, we investigated the associations of age, education, ethnic background, gender, and language on the Digit Symbol Substitution (DSS) test – a subtest of the WAIS‐R – and to provide demographically adjusted norms for a diverse group of Hispanics/Latinos. Method: The target population for the Study of Latinos‐Investigation of Neurocognitive Aging (SOL‐INCA; 2015–2018) included individuals from Central American, Cuban, Dominican, Mexican, Puerto Rican, and South American backgrounds (n = 6, 172). Average age was 63.4±8.3 years, 54.5% were female, and mean education was 11.0±4.6 years. The DSS was administered as part of a larger cognitive protocol in participants' preferred language (English or Spanish). Lower scores on the DSS are associated with slower processing speed. Demographic adjusted DSS scores, and percentile cut‐points were created using survey‐adjusted regression and quantile regression models. Result: In covaried regression models, each year increase in age was associated with B = ‐0.54 (p<0.001) units decrease in DSS scores, and each additional year of education with B = 1.42 (p<0.001) units increase in performance. Males had, on average, lower DSS scores than females (B = ‐2.41; p<0.001), and individuals with English as their preferred language performed better than those preferring Spanish (B = 6.18; p<0.001). DSS performance varied significantly by Hispanic/Latino background with, predominantly, Mexicans scoring highest and Dominicans lowest on the DSS. Conclusion: While other norms for Hispanic/Latino populations exist, results from this study represent the largest and only norms for Hispanic/Latinos living in the US. Representative DSS test norms for diverse groups of US‐based Hispanics/Latinos will advance cognitive assessment and the accuracy of neurocognitive disorder diagnosis in this country. We have developed an online dashboard to facilitate potential clinical use and interpretation (https://solincalab.shinyapps.io/DSST/ )